PROBLEMATIKA PERKEMBANGAN KOGNITIF ANAK DAN REMAJA DI ERA DIGITAL: TINJAUAN LITERATUR TENTANG DAMPAK PENGGUNAAN MEDIA SOSIAL TERHADAP KONSENTRASI DAN POLA PIKIR - Shevinda Azkia Fairish; Annisa Diah Pramesti; Kayla Zahin Aurillia; Adwinata Asafwa Putra; Ardityo Dharmawan; Denok Setyawati; Muhammad Farid Ilhamuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The exponential growth of digital technology has brought about profound shifts in how children and adolescents develop cognitively. The growing intensity of social media engagement has sparked widespread concern regarding young people’s ability to sustain attention, think critically, and process information effectively. This study seeks to conduct a comprehensive review of existing scholarship examining how social media use shapes the cognitive development of children and adolescents. A systematic literature review of peer-reviewed publications from recent years served as the primary methodology. Findings reveal that uncontrolled social media consumption tends to erode attention capacity, heighten susceptibility to distraction, and foster a more impulsive, surface-level mode of thinking. Nevertheless, social media holds genuine potential as a tool for cognitive enrichment when employed thoughtfully and with appropriate oversight. It follows that parents, educators, and counselors must take an active role in mediating young people’s relationship with digital media to ensure healthy cognitive growth.